Item Analysis of Reading Comprehension Test of Wattpad Readers and Writers Community - Rismayani, Rismayani (Journal of Literature Language and Academic Studies, 2022)
Reading is one of the four basic language skills that should be mastered by language learners. It is the ability to understand words contained in a document and make use of the knowledge for personal growth and development. To measure the learners learning progress in reading skills, normally, the test must be given periodically. It also can be used to diagnose a teacher's competence in teaching and to find out how much the learners have learned